The Effect of Consuming Ambon Bananas on Reducing Hypertension - Kolompoy, Jane Annita; Tumurang, Marjes Nitro; Lengkey, Sancia Gladies; Pesak, Ellen; Desyani, Ni Luh Jayanthi (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Background: Hypertension is a chronic disease that can affect all humans from the youngest to the oldest. Data from WHO (World Health Organization) 2015, shows about 1.13 billion people in the world suffer from hypertension. That is, 1 in 3 people in the world suffer from hypertension. In Indonesia, based on Riskesdas 2018 data, the prevalence of hypertension in Indonesia is 8.4% and based on the results of measurements in the population aged ≥ 18 years 34.1%. Hypertension cannot directly cause death, if not treated immediately, it will risk complications such as stroke, myocardial infarction, kidney failure and encephalopathy. Hypertensive disease can also be prevented and minimized with non-pharmacological therapy to avoid the side effects of antihypertensive drugs, namely with a healthy and balanced diet. One of them is by consuming adequate potassium. The fruit that contains a lot of potassium is banana ambon. The purpose of this study is to see the effect of banana ambon consumption on the level of hypertension. Methods through database searches used include Google Scholar, Garuda and Directory of Open Access Journal. The keywords used in the article search were hypertension and banana ambon. The results obtained 103 articles and only 9 articles were used in accordance with the analysis of objectives, suitability of topics, research methods used, and the results of each article. Conclusion: banana ambon has an effect in lowering blood pressure / hypertension.